2008
DOI: 10.1371/journal.pone.0002593
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic Complement Activation in Age-Related Macular Degeneration

Abstract: Dysregulation of the alternative pathway (AP) of complement cascade has been implicated in the pathogenesis of age-related macular degeneration (AMD), the leading cause of blindness in the elderly. To further test the hypothesis that defective control of complement activation underlies AMD, parameters of complement activation in blood plasma were determined together with disease-associated genetic markers in AMD patients. Plasma concentrations of activation products C3d, Ba, C3a, C5a, SC5b-9, substrate protein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
310
4
18

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(347 citation statements)
references
References 39 publications
15
310
4
18
Order By: Relevance
“…Biomarker studies reported complement activation products in AMD plasma, indicative of low-grade, systemic AP activation (39)(40)(41). Inheritance of a more active complotype may be detrimental only in the elderly, where chronic inflammation has been sustained long-term, whereas inheritance of a less active complotype, although protective against inflammation, may increase susceptibility to infection, a negative selective pressure in populations where infection is Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker studies reported complement activation products in AMD plasma, indicative of low-grade, systemic AP activation (39)(40)(41). Inheritance of a more active complotype may be detrimental only in the elderly, where chronic inflammation has been sustained long-term, whereas inheritance of a less active complotype, although protective against inflammation, may increase susceptibility to infection, a negative selective pressure in populations where infection is Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from immunocytochemical and genetic studies suggested that local activation of the complement system by drusen in combination with a dysfunctional regulation might contribute to the process of AMD (Tuo et al 2004). The fact that several groups have shown that blood of AMD patients contains raised levels of various complement factors, such as C5a, C3d and CFD, suggests that systemic complement activation is associated with AMD (Scholl et al 2008;Reynolds et al 2009;Anderson et al 2010). The exact reason for an enhanced activation of the complement system has not yet been identified although it has been hypothesized that it may be due to the association with atherosclerosis (Mullins et al 2000;Klein et al 2004;Machalinska et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms causing AMD remain unknown although inflammatory processes have been implicated as evidenced by the identification of susceptibility genes encoding complement factors (Tuo et al 2004;Klein et al 2005;Chen et al 2010;Khandhadia et al 2012) and the presence of complement proteins in drusen (Hageman et al 2001). These findings were supported by studies showing an increase in the level of various complement activation products in the circulation of AMD patients (Donoso et al 2006;Scholl et al 2008;Reynolds et al 2009;Hecker et al 2010) and provided further evidence for a systemic inflammatory component to the disease pathogenesis (Parmeggiani et al 2012). The exact relationship between AMD and the innate immune system, however, remains to be clarified.…”
Section: Introductionmentioning
confidence: 93%
“…Sera from AMD patients showed strong reactivities to a variety of complement factors. In other studies, SNPs in the genes C3 and CFH involved in complement activation were strongly associated with AMD (Scholl et al 2008, Ristau et al 2014. C3 activates the complement pathway whereas CFH serves as a regulator of complement activation, and CFH-deficient mice tend to develop ocular features characteristic of AMD compared with wild type controls (Coffey et al 2007).…”
Section: Profile Of Autoantibodies To Ocular Antigens In Patients Witmentioning
confidence: 94%